2007
DOI: 10.1038/sj.bjc.6603585
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of docetaxel, cisplatin and fluorouracil followed by carboplatin and radiotherapy in locally advanced oesophageal cancer

Abstract: This study was performed to assess the efficacy and safety of docetaxel, cisplatin and fluorouracil combination in patients with unresectable locally advanced oesophageal squamous cell carcinoma. Treatment consisted of docetaxel 60 mg m À2 , cisplatin 75 mg m À2 on day 1 and fluorouracil 750 mg m À2 day À1 on days 2 -5, repeated every 3 weeks for three cycles, followed by carboplatin 100 mg m À2 week À1 for 5 weeks and concurrent radiotherapy (45 Gy in 25 fractions, 5 days week À1 ). After radiotherapy, eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 36 publications
0
38
1
Order By: Relevance
“…The activity observed with this oxaliplatin combination is also better than that obtained in a similar patient population using docetaxel in combination with cisplatin and FU, followed by carboplatin and concurrent radiotherapy, and surgery [10]. In advanced loco-regional disease, Polee et al [33] reported 17 of the 178 patients surviving at least 3 years using diVerent cisplatinum based combinations.…”
Section: Discussionmentioning
confidence: 87%
“…The activity observed with this oxaliplatin combination is also better than that obtained in a similar patient population using docetaxel in combination with cisplatin and FU, followed by carboplatin and concurrent radiotherapy, and surgery [10]. In advanced loco-regional disease, Polee et al [33] reported 17 of the 178 patients surviving at least 3 years using diVerent cisplatinum based combinations.…”
Section: Discussionmentioning
confidence: 87%
“…However, survival remains disappointing and did not improve with the standard PF regimen. Treatment-related toxicities may compromise clinical efficacy (6). Therefore, new drugs and combinations with a better therapeutic index are required.…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase the therapeutic ratio over that of standard PF-based chemoradiotherapy, attempts have been made in a phase I/II study to incorporate next-generation cytotoxic chemotherapeutic agents, such as docetaxel (5,6). However, survival remains disappointing and did not improve with the standard PF regimen.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Although various chemotherapy regimens are available, esophageal cancer carries a very poor prognosis, with a mean survival time of less than 8.1 months. 5 Currently, neoadjuvant treatment (such as capecitabine and cisplatin with concurrent radiotherapy (RT) followed by esophagectomy) is considered the effective treatment for esophageal cancer, 6,7 leading to complete pathologic response at the time of surgical resection and improved local tumor control and eradication of micrometastases. 8 Clearly, the development of novel and potent therapeutics in/not in combination with RT to improve both local and distant tumor control in esophageal cancer is an urgent task.…”
Section: Introductionmentioning
confidence: 99%